Transnational connections of health professionals: medicoscapes and assisted reproduction in Ghana and Uganda. Issue 4 (3rd July 2016) - Hörbst, Viola; Gerrits, Trudie
ABSTRACT: Objectives . Based on our comparative fieldwork in two private fertility clinics in Accra (Ghana) and Kampala (Uganda), we explore the transnational mobility of providers involved in assisted reproductive technologies (ARTs) and analyze how resulting transnational networks influence the realization and appropriation of these therapeutic treatments. By exploring these case studies from developing countries, this article intends to contribute to the field of studies that examine the diversification and complexity of migration and health care. Design . We first summarize the dynamics affecting the health-care systems in Ghana and Uganda over the last decades. Then, we describe the transnational mobility engaged in the two clinics. Through the case studies, we highlight how ARTs are realized and appropriated in the two receiving countries, and the role transnational contacts play within the negotiations of medical ethos and financial interests. By using the concept of medicoscapes, we analyze the worldwide connections between ART providers, the institutions they work in, their medical practices, artifacts, and their regimes of medical knowledge. Result . Transnational professional contacts have been essential to the setup of both clinics offering ARTs in Ghana and Uganda. These contacts developed along colonial and post-colonial links, integrating also south–south relationship. The clinics' directors act as entrepreneurs and creative decision-makers who capitalize on their transnational professional network. The case studies show the diverse transnational entanglements in both clinics and demonstrate the frictions between the doctors' entrepreneurial interests, medical concerns and cultural values. Conclusion . The transnational professional contacts expose both clinics to varying practices and debates, and make them into sites for negotiating distinct clinical practices. They provoke frictions between entrepreneurial interests and medical concerns including cultural values. In current medicoscapes, in a situation of full absence of any form of financial support and of any national ART regulation in Ghana and Uganda, clinic directors are in the position to apply those practices that fit their interests and local circumstances best.